Tantangan dan Solusi Pendidikan Inklusi di Sumatera Utara : Mewujudkan Kesetaraan Pendidikan Untuk Semua Anak - Deswan Clever Feelly Krist Zega; Egina Shinta Bella Br. Ginting; Jessica Yolanda Lumban Gaol; Marina Gabriella Hutagalung; Natasya Agatha Putri Jawak; Shely Dwira Simorangkir; Tiurma Sania V M Munthe; Lily Tansliova (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Inclusive education in North Sumatra faces various challenges in efforts to achieve educational equality for all children, including children with special needs. This study aims to analyze the challenges and solutions applied in the implementation of inclusive education in the region. The results of the study indicate that the main challenges in inclusive education include limited facilities that support the needs of children with disabilities, the lack of teachers with special competencies, and minimal public understanding of the importance of inclusive education. Additionally, the limitations in resources and the lack of training for educators are also significant barriers to providing quality education for all children. However, several solutions have been implemented to address these issues. These solutions include improving teacher training to ensure educators have sufficient skills and knowledge in handling children with special needs, providing more supportive facilities and infrastructure such as disability-friendly classrooms, and efforts to socialize the importance of inclusive education to the community to reduce stigma against children with special needs. This study emphasizes that collaboration between the government, schools, and the community is essential to strengthen the implementation of inclusive education, in order to create a more inclusive and equitable learning environment for all children in North Sumatra.